PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP AUDIT DELAY DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI SELAMA PANDEMI COVID-19 - Aulia Bella Marinda; Rini Widianingsih; Wita Ramadhanti; Atiek Sri Purwati; Ratu Ayu Sri Wulandari (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
This research aims to determine and analyze the effect of good corporate governance on audit delay with profitability as a moderating variable. The population in this research are financial sector companies listed on the Indonesia Stock Exchange during the period 2020-2021. The sampling technique used is purposive sampling and obtained as many as 180 samples. This research used secondary data types in the form of financial reports and annual reports of each company. The data analysis technique used is multiple linear regression analysis and moderation regression analysis. The result of the research using SPSS version 25 show that: (1) Audit committee has a negative effect on audit delay, (2) Institutional ownership has a negative effect on audit delay, (3) Independent commissioners have no effect on audit delay, (4) Profitability is unable to moderate the influence of audit committee on audit delay, (5) Profitability is able to moderate the effect of institutional ownership on audit delay, and (6) Profitability is unable to moderate the effect of independent commissioners on audit delay.